Should family members be present during cardiopulmonary resuscitation [Kardiyopulmoner resüsitasyon sirasinda aile üyeleri bulunmali mi?] - (:unkn) unknown (My University, 2007)
There is increasing discussion about relatives being allowed to witness cardiopulmonary resuscitation (CPR) attemps. In 1995 the Emergency Nurses Association (ENA) developed clinical guidelines to support the option of family presence during CPR. Other health organizations, including the American Heart Association (AHA) and the American Association of Critical-Care Nurses, have since followed suit. In addition, advanced training programs such as the AHA's Advanced Cardiac Life Support Course and Pediatric Advanced Life Support Course and the ENA's Trauma Nursing Core Course and Emergency Nursing Pediatric Course have been incorporating family presence recommendations into their curricula. There is no report or published explanation regarding family member presence during CPR in Turkey.